Inclined FRP U-jackets for enhancing structural performance of FRP-plated RC beams suffering from IC debonding. (15th September 2018) - Fu, B.; Tang, X.T.; Li, L.J.; Liu, F.; Lin, G.
Abstract: Intermediate crack debonding (i.e., IC debonding) commonly controls the failure of FRP-plated RC beams. Such IC debonding often occurs with the maximum strain of the FRP soffit plate being far lower than its rupture strain, thus leading to a low utilization of the high strength of expensive FRP material. It is of increasing interest of the research and engineering community to explore an effective anchorage for enhancing the structural performance of FRP-plated RC beams suffering from IC debonding. Inclined FRP U-jacketing is among the easiest and most effective options for this purpose. This paper presents an experimental study to systematically investigate the effect of inclined FRP U-jacketing on the structural performance of FRP-plated RC beams suffering from IC debonding. Eight full-scale RC beams were tested with the width, height and inclination of the U-jacket as the experimental variables. Findings from the present tests show that inclined FRP U-jacketing could successfully lead to concrete crushing failure from IC debonding in the control specimen without anchorage, and significant increase in the load and mid-span deflection of up to 55.8% and 229% over these of the control specimen.